2002
DOI: 10.1029/2001jd000958
|View full text |Cite
|
Sign up to set email alerts
|

Modeling approaches to assimilating L band passive microwave observations over land surfaces

Abstract: [1] L band passive microwave remotely sensed data have great potential for providing estimates of soil moisture with high temporal sampling and on a regional scale. Several studies have shown the possibility of assessing the hydrological conditions deep down in soil (in the top 1 or 2 m) from these repetitive estimates of surface soil moisture. Water availability for plants, which is related to soil moisture in the root zone, is a key variable for estimating the evapotranspiration fluxes over land surfaces. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…This problem may be the major drawbacks for implementing variational assimilation procedures. It may be solved, at least in some situations, if a careful sensitivity analysis of the assimilation procedure is done in order to define precisely the parameters that should be retrieved or if some parameters are known from previous studies as for example in Wigneron et al (2002). Olioso et al (1999a,b) showed, with another model, that parameter compensations might be used on purpose for reducing the number of parameters to retrieve without affecting the accuracy of estimated evapotranspiration.…”
Section: Discussionmentioning
confidence: 97%
“…This problem may be the major drawbacks for implementing variational assimilation procedures. It may be solved, at least in some situations, if a careful sensitivity analysis of the assimilation procedure is done in order to define precisely the parameters that should be retrieved or if some parameters are known from previous studies as for example in Wigneron et al (2002). Olioso et al (1999a,b) showed, with another model, that parameter compensations might be used on purpose for reducing the number of parameters to retrieve without affecting the accuracy of estimated evapotranspiration.…”
Section: Discussionmentioning
confidence: 97%
“…Cayrol et al (2000) assimilated series of AVHRR surface reflectances and temperatures to calibrate a coupled SVAT-Vegetation growth model. More recently, Wigneron et al (2002) assimilated L band passive brightness temperature in the ISBA-Ags model (Calvet et al, 1998), coupled with the Tau-Omega microwave radiative transfer model, in order to retrieve initial soil moisture and a parameter controlling vegetation growth.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating this variable at the global scale has potential applications in hydrology and meteorology [Fennessy and Shukla, 1999;Dirmeyer, 2000;Leese et al, 2001]. Several studies showed that time series of surface soil moisture (wg) can be used to retrieve the rootzone soil moisture by using an assimilation algorithm [Entekhabi et al, 1994;Calvet and Noilhan, 2000;Wigneron et al, 2002a]. A number of airborne and ground-based experiments have shown that L-band passive microwave remotely sensed brightness temperatures (T B ) have great potential for providing estimates of wg.…”
Section: Introductionmentioning
confidence: 99%